Evangelical millennialism in the trans-Atlantic world, 1500 - 2000 - Gribben, Crawford 1974- (Palgrave Macmillan, 2011)
This title offers the first complete overview of the intellectual history of one of the most significant contemporary cultural trends - the apocalyptic expectations of European and American evangelicals - in an account that guides readers into the origins, its evolution, and its revolutionary potential in the modern world